PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PEMERINTAH DESA SITUSARI KECAMATAN CILEUNGSI KABUPATEN BOGOR - Turah Slamet; Maulia Ratu Zahra (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the effect of Work Motivation and Work Discipline on the Performance of Government Employees in the Situsari Village, Cileungsi District, Bogor Regency. The research was conducted at the Situsari Village Office, Cileungsi District, Bogor Regency. The sample used in this study amounted to 25 respondents. This study uses saturated sampling techniques and data analysis with multiple linear regression. Hypothesis testing uses the T test and F test with the help of the SPSS version 26.0 application program. The results of multiple linear regression indicate that \Work Motivation has a positive and significant effect on employee performance. Work Discipline has a positive and significant effect on Employee Performance. Based on the results of the F test, it shows that motivation and work discipline simultaneously have a significant effect on employee performance. And the coefficient of determination of influence is 72.9%.